Development and Evaluation of A New Studio-Based Course on Critical Design - Aykut Coskun (Journal of Visual Art and Design, 2018)
Although the last decade has seen critical design growing as an area of research, studies have rarely focused on how to teach it. Some design schools have established graduate programs and others have developed individual undergraduate courses on critical design. However, to date there has been no study that investigated student reactions to the learning of critical design. Addressing this gap, this paper proposes a new studio-based course at the graduate level aimed at providing students with a medium for critical discussion and creative reflection on contemporary social issues. Lectures, seminars and class discussions were used to instruct theoretical concepts pertaining to critical design, while a 10-week design studio project was used to concretize these concepts. The students' initial reactions to this teaching methodology was gathered through semi-structured interviews conducted at the end of the course. The interview results indicate that students had a very positive attitude towards critical design and the course. Furthermore, although understanding critical design was a major challenge for them, the teaching methods used in the course (i.e. lectures, critical design assignment and reflection paper) helped them overcome this challenge. Finally, this paper offers suggestions for design educators for constructing critical design courses that meet design students' expectations.